2010
DOI: 10.1177/1368430209344867
|View full text |Cite
|
Sign up to set email alerts
|

Gender moderates the self-regulatory consequences of suppressing emotional reactions to sexism

Abstract: This study examined whether members of low-status, stigmatized groups are less susceptible to the negative cognitive consequences of suppressing their emotional reactions to prejudice, compared with members of high-status, non-stigmatized groups. Specifically, we examined whether regulating one s emotional reactions to sexist comments—an exercise of self-regulation—leaves women less cognitively depleted than their male counterparts. We hypothesized that the greater practice and experience of suppressing emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Sexual harassment had also a more negative effect on self-perceived health for men than women (Shipherd et al, 2009). Other authors have commented that because women are more used to sexual harassment, they have learned to live with it, whereas men find sexual harassment unexpected (de Haas, Timmerman, & Hoeing, 2009; Johnson, Mitchell, Bean, Richeson, & Shelton, 2010). Our study is the first to show this trend in a southern European country, in a university student sample.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual harassment had also a more negative effect on self-perceived health for men than women (Shipherd et al, 2009). Other authors have commented that because women are more used to sexual harassment, they have learned to live with it, whereas men find sexual harassment unexpected (de Haas, Timmerman, & Hoeing, 2009; Johnson, Mitchell, Bean, Richeson, & Shelton, 2010). Our study is the first to show this trend in a southern European country, in a university student sample.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these studies revealed that during service simulations, subjects performed significantly (p < .01) worse on cognitive tasks when they were instructed to "act friendly" towards difficult clients than when instructed to "act naturally." Secondly, moderate negative effects of emotion regulation were also found one step lower in the hierarchy of relevance (Johnson et al, 2010;Pearson et al, 2013;Perbandt, 2007;Richards et al, 2003). It concerned four experiments with non-service interactions.…”
Section: Evidence Of the Cognitive Side Effects Of Emotion Regulationmentioning
confidence: 99%
“…This is necessary because knowledge is scattered over various research areas, such as social psychology (e.g. Johnson et al, 2010) occupational health psychology (e.g. Goldberg & Grandey, 2007) and cognitive psychology (e.g.…”
Section: The Current Reviewmentioning
confidence: 99%
“…However, coping with workplace stigma has many aspects: constant vigilance for threat, especially among those highly identified with their stigmatized group (Begeny and Huo, 2017, 2018); managing and suppressing stereotype-relevant thoughts and feelings; effectively negotiating threatening contexts; choosing to confront or not confront bias; avoiding mistakes and the confirmation of group-relevant stereotypes; and more generally regulating threat (emotional coping, accepting, or resisting). To some degree, targets can become better at – and habituated to – responding to stigma, such that those who have more frequent experiences and practice dealing with stigma become better at doing so and suffer fewer cognitive costs (Crisp et al, 2009; Johnson et al, 2010). Nevertheless, all of these aspects take cognitive and emotional energy and can eventually lead to exhaustion (e.g., Schmader and Johns, 2003; Johns et al, 2008; Logel et al, 2009; Ståhl et al, 2012a; Hall et al, 2015; c.f., Baumeister et al, 1998; Muraven and Baumeister, 2000).…”
Section: Potential Hidden Costs Of Dealing With Stigmamentioning
confidence: 99%